Emerging Dynamics in Tourism Industry Workforce Mobility in Southern Cross River State, Nigeria - Akeh, Linus Beba (Mediterranean Journal of Social Sciences, 2021)
The challenge of brain drain/workforce mobility/out-migration in tourism and hospitality industry workforce is a rising phenomenon. The study investigated the factors responsible for the emerging dynamics in tourism industry workforce mobility in Southern Cross River, Nigeria. Data was generated through the administration of structured questionnaire and oral interviews on the staff and workforce of tourism industry. The results revealed that on aggregate, a total of 63.50% workers had intentions to migrate from their job while 36.50% workers had no intention to migrate from their current job. Further findings revealed that low remuneration, unfavourable working hours, stress, lack of career prospects, lack of job security, unsatisfactory working conditions, health risk, and challenge of job matching were among the reasons for job out-migration among the industry workforce. The study recommended that both public and private sectors should create enabling tourism work-environment for retention of tourism employees. Received: 14 August 2021 / Accepted: 2 October 2021 / Published: 5 November 2021